The occurrence of muskrat Ondatra zibethicus in central and eastern Poland in the period 1996–2007 - Romanowski, Jerzy; Karpowicz, Karolina (Studia Ecologiae et Bioethicae, 2020)
Muskrat, Ondatra zibethicus (L. 1766), is an introduced species to European fauna. It is widespread in Poland, however, signs of its decline were observed in the last decades. While most of the information on muskrat is based on questionnaires and bag record, in this paper results of field census for muskrat signs (tracks and faeces) at a total of 1554 sites are presented. Signs of muskrats were present at 19.5% of 1111 sites surveyed from 1996-1998, and at 5.3% of 413 sites surveyed in 2007. Muskrats inhabited mostly small and medium rivers in the western part of the study area. The decrease in the occurrence of the species over a study period is the best document by a significant reduction in the frequency of muskrat records at the 249 sites surveyed in 1996-1998 (present at 44% sites) and 2007 (7%). The decline of the muskrat population is most probably the effect of increasing predation by American mink Neovison vison.